Low-Dose Gallic Acid Administration Does Not Improve Diet-Induced Metabolic Disorders and Atherosclerosis in Apoe Knockout Mice - Jie Bai; Qiu-Yue Lin; Xiangbo An; Shuang Liu; Yao Wang; Yunpeng Xie; Jiawei Liao (Journal of Immunology Research)
Diets rich in polyphenols are known to be beneficial for cardiovascular health. Gallic acid (GA) is a plant-derived triphenolic chemical with multiple cardio-protective properties, such as antiobesity, anti-inflammation, and antioxidation. However, whether GA could protect against atherosclerotic cardiovascular diseases is still not defined. Here, we investigated the effects of low-dose GA administration on diet-induced metabolic disorders and atherosclerosis in the atherosclerosis-prone apolipoprotein E (Apoe) knockout mice fed on a high-fat Western-type diet (WTD) for 8 weeks. Our data showed that GA administration by oral gavage at a daily dosage of 20 mg/kg body weight did not significantly ameliorate WTD-induced hyperlipidemia, hepatosteatosis, adipogenesis, or insulin resistance; furthermore, GA administration did not significantly ameliorate WTD-induced atherosclerosis. In conclusion, our data demonstrate that low-dose GA administration does not elicit significant health effect on diet-induced metabolic disorders or atherosclerosis in the Apoe knockout mice. Whether GA could be beneficial for atherosclerotic cardiovascular diseases therefore needs further exploration.